GIS Mapping and Monitoring of Cellular Communication Quality in Terms of Crowdsourcing - Zanozin Viktor Valeryevich; Shabanov Dmitriy Ivanovich; Iolin Mikhail Mikhaylovich; Borzova Anastasiya Sergeevna; Agoshkova Elena Vasilyevna (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 11. Estestvennye Nauki, 2015)
At the present day the monitoring of mobile services quality is carried out in the framework of the internal audit of the enterprise communications. The Federal Service for Supervision of Communications, Information Technology and Mass Communications (Roskomnadzor) does not yet have high-quality assurance techniques of services and conducts partial spot checks on the basis of existing normative legal acts (NLA). One of cellular communication quality monitoring method is Netmonitoring. Netmonitoring, as one of the possible types of quality control services provided by mobile operators, is described in this article. Netmonitoring is provided in the Astrakhan city on the Kirova street, Savushkina street, Kubanskya street, Magistralnaya street and other large streets of the city. There are more than 150 cellular level measurements. Netmonitoring is based on crowdsourcing and mobile mapping. Mobile mapping is the process of collecting geospatial data using mapping sensors mounted on a mobile platform. The search of base stations was carried out by means of such programs as Netmonitoring, Network Signal Info and Antennas. The resulting data, namely the network code, “cell ID” and local area code, were used for geo-information programs creation. The experience in designing KML and Visual Basic languages programs Netmonitoring and AstraNetMonitoring is described in this paper.